2019
DOI: 10.1371/journal.pone.0226263
|View full text |Cite
|
Sign up to set email alerts
|

Swaying slower reduces the destabilizing effects of a compliant surface on voluntary sway dynamics

Abstract: The ability to control weight shifting (voluntary sway) is a crucial factor for stability during standing. Postural tracking of an oscillating visual target when standing on a compliant surface (e.g. foam) is a challenging weight shifting task that may alter the stability of the system and the muscle activation patterns needed to compensate for the perturbed state. The purpose of this study was to examine the effects of surface stability and sway frequency on the muscle activation of the lower limb, during vis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
16
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 63 publications
1
16
0
Order By: Relevance
“…We detected maximal joint moments between 100 and 500 Nm, which are substantially higher compared to the joint moments reported for postural swaying (Hess et al, 2006 ) and equivalent to running (Stefanyshyn and Nigg, 1998 ; Arampatzis et al, 1999 ), jumping (Nikolaidou et al, 2017 ), and landing (Walsh et al, 2011 ; Werkhausen et al, 2018 ). Recently, we found greater movement instability and higher EMG activity of the leg muscles in unstable ground conditions during postural tracking of an oscillating visual target (Patikas et al, 2019 ). The higher activation of the leg muscles was the consequence of the increased movement instability during postural swaying on unstable ground and was interpreted as a compensation mechanism to ensure balance in the presence of external perturbations (Patikas et al, 2019 ).…”
Section: Discussionmentioning
confidence: 86%
“…We detected maximal joint moments between 100 and 500 Nm, which are substantially higher compared to the joint moments reported for postural swaying (Hess et al, 2006 ) and equivalent to running (Stefanyshyn and Nigg, 1998 ; Arampatzis et al, 1999 ), jumping (Nikolaidou et al, 2017 ), and landing (Walsh et al, 2011 ; Werkhausen et al, 2018 ). Recently, we found greater movement instability and higher EMG activity of the leg muscles in unstable ground conditions during postural tracking of an oscillating visual target (Patikas et al, 2019 ). The higher activation of the leg muscles was the consequence of the increased movement instability during postural swaying on unstable ground and was interpreted as a compensation mechanism to ensure balance in the presence of external perturbations (Patikas et al, 2019 ).…”
Section: Discussionmentioning
confidence: 86%
“…It has been reported that external perturbations increase movement instability and challenge the neuromotor system during motion. [32][33][34] As a response, the neuromotor system modifies the motor control and increases the systems robustness (ie, ability to cope with perturbations 32,33 ). Recently, we found that, in the presence of perturbations, the central nervous system generates fuzzier, less unstable, and less complex basic activation patterns of muscle groups, which makes the motor execution less prone to the influence of disturbances.…”
Section: Discussionmentioning
confidence: 99%
“…Challenging conditions, as for example the exposure to external perturbations, enhance the demand for the sensorimotor system to perceive sensory signals and to generate appropriate motor commands. It has been reported that external perturbations increase movement instability and challenge the neuromotor system during motion 32‐34 . As a response, the neuromotor system modifies the motor control and increases the systems robustness (ie, ability to cope with perturbations 32,33 ).…”
Section: Discussionmentioning
confidence: 99%
“…In the presence of external mechanical perturbations, the local dynamic stability during walking 10 , 12 , 13 , running 10 and balance tasks 7 , 14 decreases. At the same time, electromyographic (EMG) activity and muscle coactivation increases 14 16 , indicating a modulation of the neuromotor control in the presence of perturbations. Furthermore, during perturbed conditions the basic activation patterns of muscle groups become wider increasing the temporal overlap of activation between chronologically adjacent muscle synergies 10 , 17 , 18 .…”
Section: Introductionmentioning
confidence: 99%
“…Oullier et al 26 using the moving room paradigm found a decrease in the room-head coupling with increasing room frequency depicting a demand-dependent deterioration of visual coupling performance. While the effect of unstable surfaces on postural control during quiet stance has been widely investigated 14 , 21 , 27 , 28 , there is still a gap in the literature regarding possible modulations of motor control in the presence of perturbations during more complex tasks, such as visually guided postural sway, especially when the target is moving with high complexity.…”
Section: Introductionmentioning
confidence: 99%